2021
DOI: 10.1186/s42506-021-00093-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of education through nurse-led telephone follow-up (telenursing) on the quality of life of COVID-19 patients

Abstract: Abstracts Background The widespread prevalence of COVID-19 has disrupted the social life, physical function, and daily activities of patients, leading to reduced quality of their lives. Because of the nature of this disease and its comprehensive impact on patients’ lives, a follow-up based on the conditions of these patients is necessary. This study was conducted to determine the impact of nurse education and telephone follow-up (telenursing) on the quality of life of COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(15 reference statements)
0
7
0
2
Order By: Relevance
“…In the current study, the intervention group had improved quality of life, although the difference was not statistically significant. Raesi et al (2021) also found a telephone follow-up improved quality of life of COVID-19 patients, and Behzad et al (2016) found improved quality of life for patients with hypertension using an empowerment program based on telenursing care. It may be that quality of life for patients at severe stages of COPD may require long-term interventions to be effective.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, the intervention group had improved quality of life, although the difference was not statistically significant. Raesi et al (2021) also found a telephone follow-up improved quality of life of COVID-19 patients, and Behzad et al (2016) found improved quality of life for patients with hypertension using an empowerment program based on telenursing care. It may be that quality of life for patients at severe stages of COPD may require long-term interventions to be effective.…”
Section: Discussionmentioning
confidence: 98%
“…Telenursing has been considered a potential solution to service delivery challenges during the COVID-19 pandemic, mainly due to its compliance with physical distancing measures and stay-at-home orders implemented by several governments to curb the spread of infection. Additionally, telenursing is benefit for the nurse to providing telenursing care for victims in disasters in a simulated study for introducing of possibility nursing interventions, telenursing education on nurses' compliance with standard precautions during the COVID-19 pandemic [1], telenursing training based on family-centered empowerment pattern on compliance with diet regimen in patients with diabetes mellitus, education through telenursing can increase the quality of life of COVID-19 patients [2], telenursing in COVID-19 times and maternal health: whatsapp® as a support tool, telenursing on attachment and stress in mothers of preterm infants, telephone-based telenursing on perceived stressors among older adults receiving hemodialysis, telenursing on levels of depression and anxiety in caregivers of patients with stroke, Treatment of Obesity Among Youth With Intellectual and Developmental Disabilities: An Emerging Role for Telenursing [3], Telenursing intervention increases psychiatric medication adherence in schizophrenia outpatients [4]. Telenursing are ongoing to increase both nationally and internationally.…”
Section: Introductionmentioning
confidence: 99%
“…Patient participation is a patient's subsequent action adherence to the health providers' recommendation. Nevertheless, there is little evidence that documents the impact of a nurse-led COVID-19 rapid response telephone triage center on patient participation with the recommendations, and few studies have examined factors associated with patient participation with the COVID-19 triage recommendations [8,9].…”
Section: Introductionmentioning
confidence: 99%